Whole-Plant Water Use in Field Grown Grapevine: Seasonal and Environmental Effects on Water and Carbon Balance - Douthe, Cyril; Medrano, Hipólito; Tortosa, Ignacio; Escalona, Jose Mariano; Hernández-Montes, Esther; Pou, Alicia (Frontiers in Plant Science, 2018)
Water scarcity is a main challenge in vineyards sustainability in most of the grapevine areas now and even more in near future due to climatic change . In consequence, water use efficiency measurements are of the highest interest to improve the sustainability of this crop. The vast majority of water use efficiency measurements relays on measurements of leaf carbon and water fluxes at leaf level. However, less data are available at the whole-plant level, and for the moment those data are not totally coincident with conclusions reached at leaf scale. In this study we used whole-plant chambers able to enclose an entire plant of 12 years-old to measure at the same time water and carbon fluxes under realistic field grown conditions. The main objectives were to identify the technical issues interfering the whole-plant measurements and track the environmental and other abiotic factors that can affect water and carbon balance, i. e. water use efficiency at the whole-plant scale. To achieve those objectives, we measured whole-plant water and carbon fluxes in grapevine exposed to two different water regimes at three phenological stages (pea size (July), ripening (August) and harvest (September)). In September, measurements were repeated under high CO2 to also check its effect at the whole-plant scale. The results indicate that water and carbon fluxes are well coordinated under both water availability treatments. Under drought conditions, both fluxes were drastically reduced, but surprisingly the estimated water use efficiency resulted not improved but decreased, contrarily to what is shown at the leaf scale. The phenology (September) also strongly decreased both water and carbon fluxes when compared to measurements in July. We hypostatized that harvest load respiration rates could have an important weight on the whole-plant net carbon exchange (NCE). Finally, high CO2 measurements, after correction for leaks, indicated an increase of whole-plant NCE as well as increased whole-plant water use efficiency, as expected. Several technical issues were identified, like 1/ instability of [CO2] during the night period that prevent robust estimation of whole-plant respiration and 2/ condensation during last night and sun-rise hours which may affect the estimation of daily plant transpiration.